2021
DOI: 10.1002/jsfa.11445
|View full text |Cite
|
Sign up to set email alerts
|

Identification of in vitro angiotensin‐converting enzyme and dipeptidyl peptidase IV inhibitory peptides from draft beer by virtual screening and molecular docking

Abstract: BACKGROUND: Hypertension and diabetes are two kinds of senile diseases which often occur simultaneously. The commonly used drugs in clinic may produce certain side effects. Food-derived polypeptide is a kind of polypeptide with great development potential, which has many functions of regulating human physiological function. Beer is rich in nutrition but there are few researches on bioactive peptides in beer.RESULTS: In this study, a rapid virtual screening method was established to obtain bioactive peptides fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The gradient was set as follows: 0–3 min, 5.0% B; 3–10 min, 5.0–10.0% B; 10–15 min, 10–20.0% B; 15–20 min, 20–95% B; 20–22 min, 95–5.0% B; 22–25 min, 5.0% B. Other mass parameters were set with reference to a previous study . Peaks Studio 8.0 software (Bioinformatics Solutions, Inc., Waterloo, ON, Canada) was used to analyze and process the MS data.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The gradient was set as follows: 0–3 min, 5.0% B; 3–10 min, 5.0–10.0% B; 10–15 min, 10–20.0% B; 15–20 min, 20–95% B; 20–22 min, 95–5.0% B; 22–25 min, 5.0% B. Other mass parameters were set with reference to a previous study . Peaks Studio 8.0 software (Bioinformatics Solutions, Inc., Waterloo, ON, Canada) was used to analyze and process the MS data.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Emodin (82), an anthraquinone, rosmarinic acid (99), a phenylpropanoid, and some stilbenoids are among the most active polyphenols; some of these compounds have shown antidiabetic effects in vivo and in vitro targeting other enzymes and receptors involved in glucose metabolism.…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
“…In this review, we will focus only on those peptides originating from vegetal dietary proteins, which according to a few investigations, can inhibit DPP-IV in vitro. [78][79][80][81] The most active peptides found in this review are summarized in Table 2, [82][83][84][85][86][87][88][89][90][91] which includes amino acid sequences, inhibitory activities, positive controls, and natural sources.…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
“…35 Several studies have demonstrated that DPP-IV is highly specific for Pro residues at the P1 position (the second amino acid residue in NH 2 terminal of peptide) and will preferentially cleave dipeptides containing alanine (Xaa-Ala; where Xaa is any amino acid) or proline (Xaa-Pro) from the N terminus of the peptide. 7 Dipeptidyl peptidase-IV also has a cleavage ability for peptides containing Ser, Gly, and Val at this position. 36,37 Although longer peptide sequence lengths have been reported to increase the inhibitory activity of DPP-IV, the IC 50 values of PGVGGPLGPIGPCYE 22 and TQMVDEEIIMEKFR 10 were 116.1 μM and 63.14 μM, respectively.…”
Section: Identification Of the Dpp-iv Inhibitory Peptidesmentioning
confidence: 99%
“…6 However, several adverse drug reactions, such as headaches, infection of the upper respiratory tract, and vascular problems, have been identified in patient populations administered these drugs on a long-term basis. 7 Although not as effective as synthetic drugs, the bioactive peptides released from food proteins could cause fewer undesirable side effects. 8 The search for fresh, efficient, and safe DPP-IV inhibitors to replace these synthetic drugs has therefore garnered increased interest.…”
Section: Introductionmentioning
confidence: 99%